Correlation of Paulo Freire's Educational Philosophy to Islamic Educational Philosophy - H, Jusniati; Helmiah, Andi Sarifah; Nurfadillah, Nurfadillah (Journal La Edusci, 2023)
Paulo Freire's philosophy of education, known as Pedagogy of the oppressed, is a conceptual narrative closely related to the philosophy of humanism. The education of the oppressed has a simple understanding, which is education that liberates or is anti-dehumanizing. One of the approaches used by Paulo Freire to address the problem of dehumanization in Brazilian society is literacy education, which, according to Freire, involves not only reading the word but also reading the world. Freire's literacy practice is not limited to formal learning in schools but is also carried out through social interaction and daily activities. This study is qualitative research with a literature review approach. Furthermore, the data sources in this study were obtained from primary, secondary, and preliminary sources, which were then analyzed by reducing all the collected data. Paulo Freire's philosophy of education is constructed upon ontology, epistemology, and axiology, which correlate with the philosophy of Islamic education. After analyzing, some weaknesses were also found in Paulo Freire's concept of education regarding its humanism as a perspective in understanding educational issues. The practice of Paulo Freire's philosophy of education also resembles normative guidance on education, and it tends to lack a final goal, relying solely on the critical consciousness of the learners in interpreting reality.